Object recognition system by depth camera using k-nearest neighbors and naïve Bayes classification for robot - Jareanpon, Chatklaw (Health Science, Science and Technology Reviews, 2016)
Today, the robot technology is used for many applications. The robot is expected to dwell in human society with the abilities such as perception, decision, and non-injury. The study aims to determine the efficiency of the robot object recognition using k-nearest neighbor (KNN) and naïve Bayes classification. The red, green, and blue (RGB) camera of microsoft kinect sensor was use to classify the detail. The experimental showedthe accuracy rate of KNN was 77.0% while the naïve Bayes classification was 60.4%.